Utilização de plasma sanguíneo na dieta de frangos de corte - Silva, Luzia Trajano da (2015)
The objective was to study the inclusion of pig blood plasma in the diet of broiler chickens from lots of arrays of different ages (36 and 56 weeks), created in recycled litter and high density housing (12 birds / m 2). 6,000 chicks from Cobb ®500 line with one day of age were used. The treatments were arranged in a factorial scheme (2x4), two ages arrays (36 and 56 weeks) and four plasma supply levels (0%, 1.0%, 0.5% and 0.25%) and were distributed in experimental units according to a completely randomized design. The stages of evaluation were: 1-7; 8-14; 15-21; 22-33 and 34-44 days. Performance reviews were measured, microbiology, histology and economic analysis. Breeder age influenced the final weight, weight gain and feed conversion up to 21 days, influenced height of villi to 44 days, crypt depth at seven, 21 and 44 days, was no effect on the weight of the eviscerated carcass, breast weight and breast yield. Inclusion of plasma in the diet influence the final weight, weight gain and feed intake up to 14 days of age no influence for all histological variables throughout the experimental period except the number of goblet cells was not influenced by the phase 21 day, had no effect on the weight of the eviscerated carcass weight and breast yield. The interaction of the matrix age and the inclusion of blood plasma in the diet, body weight and weight gain until 14 days of age, the feed intake was influenced at all stages of evaluation and have an influence on the mortality rate. The presence of Escherichia coli in cloacal swab and yet cecal and Salmonella spp was found. in the cecal contents to seven days. At 14 days was verified presence of E. coli in poultry manure and Salmonella spp. the bed and cecal contents. At 21 days, Escherichia coli and Salmonella spp in swab. and all biological materials. After 44 days there were presence of Escherichia coli in swab and cecal contents and Salmonella spp. in all biological materials. Blood plasma influences the histological parameters and improves performance, should be provided to the seven days of age birds from old arrays and up to 21 days of age birds from young breeders.